PENGARUH SIKAP KERJA DAN KEMAMPUAN DIRI TERHADAP KINERJA PEGAWAI DENGAN STRES KERJA SEBAGAI VARIABEL MODERASI (STUDI PADA KANTOR DISTRIK NAVIGASI KELAS I BELAWAN) - Refni Handayani (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The formulation of problem in this research there is influence  of work attitude on job stress. There is influence  of self ability on job stress. There is  work attitude on employees performance. There is  self ability on employees performance. There is  job stress on employees performance. The purpose of this research is for know influence and analize of   work attitude on job stress. For know influence and analize   of self ability on job stress. For know influence and analize of  work attitude on employees performance. For know influence and analize of self ability on employees performance. For know influence and analize of   job stress on employees performance. The sample in this research is 62 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result  is work attitude variable influence positive and don’t significant on job stress. Self ability variable influence negative and don’t significant on job stress. Work attitude variable influence positive and  significant on employees performance. Self ability variable influence positive and  significant on employees performance. Job stress  variable influence positive and  don’t significant on employees performance. Work attitude and self ability variable influence positive and  significant on employees performance with job stress as moderasi variable